Thermodynamic and optical parameters of the RF pulse excited slab-waveguide CO2 laser - Wojaczek, Dorota A.; Pliński, Edward F.; Witkowski, Jerzy S. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
In the paper, changes of the optical and thermodynamic parameters, such as a refractive index, pressure, and temperature are investigated on an RF pulsed CO2 slab-waveguide laser. Changes of the refractive index, and pressure are measured with a Mach–Zehnder interferometer, and microphone, respectively. A Gladstone–Dale formula is applied to calculate the changes of the temperature. It is shown how an acoustic wave in the laser cavity modifies the pressure of the laser medium in the course of the pulse duration. The results of measurements allow explaining a line hopping effect observed during the laser plasma pulse evolution.
Optica Applicata, Vol. 35, 2005, nr 2, s. 215-224
Keywords: optyka; CO2 laser; slab-waveguide; RF excitation; pulse operation; acoustic wave; line hoppings